The illustrated directory of warships from 1860 to the present - Miller, David (David M.O.) (Salamander, 2001)
Covering every major warship type from the American ironclads of the 1860s through today's super-sophisticated aircraft carriers, this fact-filled directory describes more than 200 fighting vessels, providing technical specifications along with development and service histories. Intricately detailed full-color drawings vividly bring the warships to life, while contemporary photographs depict the vessels at sea and in combat.